OD SEULU DO SYDNEY – POLITYCZNY WYMIAR IGRZYSK OLIMPIJSKICH 1988-2000 - Jung, Rafał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article aims to identify political problems and their solutions that were introduced by the International Olympic Committee (IOC) between 1988 and 2000. Throughout this time the Summer Olympic Games were held in Seul, Barcelona, Atlanta and Sydney. Especially the first two events took place during a critical period for the international relations. The geopolitical changes that resulted from it also significantly affected the world of sport. Thanks to clever diplomacy carried out by the IOC president, Juan Antonio Samaranch, the international olympic movement successfully handled the problems, achieving the status of the most powerful non-governmental organization in the world.